Hybrid repair of proximal subclavian artery transection. (October 2020) - Staniszewska, Aleksandra; Anwar, Muzaffar; Hamady, Mohamad; Nott, David
Although rare, subclavian artery injuries are associated with significant mortality and morbidity, with almost two-thirds of patients dying before reaching hospital. Recent advances in technology have resulted in increasing use of endovascular therapy in management of these injuries. In this report, we present a case of a successful hybrid repair of traumatic left proximal subclavian artery transection. The employment of an Amplatzer Vascular Plug to control a short proximal subclavian artery stump and subsequent ligation of the distal segment of subclavian artery with its anastomosis to the carotid artery resulted in excellent clinical outcome without performing a sternotomy in a young patient.